2009
DOI: 10.1162/jeea.2009.7.2-3.649
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Risk Aversion and Ambiguity Aversion

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

53
313
3
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(385 citation statements)
references
References 22 publications
(27 reference statements)
53
313
3
16
Order By: Relevance
“…Turning first to ambiguity aversion (α), we find that men are more ambiguity averse than women, consistent with the experimental results in Borghans et al (2009). Ambiguity aversion is positively related to risk aversion, but the correlation is low and ambiguity aversion is not subsumed by it.…”
Section: Estimating the α-Maxmin Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…Turning first to ambiguity aversion (α), we find that men are more ambiguity averse than women, consistent with the experimental results in Borghans et al (2009). Ambiguity aversion is positively related to risk aversion, but the correlation is low and ambiguity aversion is not subsumed by it.…”
Section: Estimating the α-Maxmin Modelsupporting
confidence: 85%
“… 29 Borghans et al (2009) find that men are more ambiguity averse than women in a sample of 347 high school students. In a study of the Dutch population, Dimmock et al (2015b) estimate the relation between ambiguity attitudes and control variables; there, however, few effects are statistically significant (sample size: N =666).…”
mentioning
confidence: 95%
“…Secondly, personality reflects generally stable patterns in behavior, motivation, and cognition (Borghans et al, 2009; Zillig, Hemenover & Dienstbier, 2002). Borghans, Golsteyn, Heckman and Meijers (2009) conducted an experiment on a sample of 347 Dutch high school students; they showed that the differences in cognitive and non-cognitive personality traits, such as IQ, the Big Five (openness, conscientiousness, extraversion, agreeableness, neuroticism), and self-control accounted for the differences in preference parameters. Zuckerman (2007) also found that differences in sensation-seeking personality traits (i.e.…”
mentioning
confidence: 99%
“…Researchers have also linked experimental behavior to the results of testing such for IQ (Oechssler et al, 2009; Brañas-Garza et al, 2012, 2015), social intelligence (Takagishi et al, 2010), and personality (Almlund et al, 2011; Rustichini et al, 2012). However, the findings are not consistent with one another (Ben-Ner et al, 2007; Eckel and Grossman, 2008; Borghans et al, 2009; Hirsh and Peterson, 2009; Oechssler et al, 2009; DeAngelo et al, 2015). …”
Section: Introductionmentioning
confidence: 73%